Yoga Prenatal Meningkatkan Kebugaran Fisik dan Psikis pada Ibu Hamil: Literatur Reviu - Yunita Laila Astuti; Husnul Khatimah; Vini Yuliani (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Prenatal yoga began to be widely developed and carried out to overcome conditions that occur in pregnant women. Yoga during pregnancy not only helps to improve the fitness of pregnant women physically, but also psychologically. The purpose of this study is to explore prenatal yoga in improving the fitness of pregnant women, both physiological and psychological aspects. This research is a literature review with article sources from international journals in 2019-2022. Articles were accessed through online databases, including Science Direct, Proquest, Springer Link, Clinical Key, and Ebsco Host from May 2 to May 10, 2022. The keywords used in the search were prenatal yoga and pregnancy. A total of 2959 articles were obtained from search results, and then identified based on inclusion and exclusion criteria. Articles that met the inclusion criteria were in the form of English experimental research that examined the benefits of prenatal yoga in pregnancy and could be fully downloaded. Articles that did not meet the criteria were eliminated after screening the title, abstract, and full-text thoroughly. Five articles met the criteria. The results of the literature review showed that prenatal yoga could improve the quality of sleep for pregnant women, reduce anxiety, depression, and distress, increase the functional index of uterine arteries, reduce maternal and neonatal complications, strengthen relationships with other pregnant women in yoga classes, and strengthen the attachment relationship between mother and fetus. Thus, it can be concluded that prenatal yoga is a useful exercise for pregnant women so that its implementation must continue to be promoted for antenatal care.